2006
DOI: 10.1128/aem.72.2.1045-1054.2006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Expression of Genes Encoding a Novel Dioxygenase Involved in Low- and High-Molecular-Weight Polycyclic Aromatic Hydrocarbon Degradation in Mycobacterium vanbaalenii PYR-1

Abstract: Mycobacterium vanbaalenii PYR-1 is able to metabolize a wide range of low-and high-molecular-weight (HMW) polycyclic aromatic hydrocarbons (PAHs). A 20-kDa protein was upregulated in PAH-metabolizing M. vanbaalenii PYR-1 cells compared to control cultures. The differentially expressed protein was identified as a ␤ subunit of the terminal dioxygenase using mass spectrometry. PCR with degenerate primers designed based on de novo sequenced peptides and a series of plaque hybridizations were done to screen the M. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 66 publications
6
123
0
6
Order By: Relevance
“…The most extensively characterized group of pyrene dioxygenase genes, a highly conserved group called nidAB genes, has been identified in certain Mycobacterium species which have been characterized for their ability to degrade high molecular weight PAH (Heitkamp et al, 1988;Khan et al, 2001;Kim et al, 2006). The biochemical pathways of pyrene degradation by Mycobacterium have also been identified Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The most extensively characterized group of pyrene dioxygenase genes, a highly conserved group called nidAB genes, has been identified in certain Mycobacterium species which have been characterized for their ability to degrade high molecular weight PAH (Heitkamp et al, 1988;Khan et al, 2001;Kim et al, 2006). The biochemical pathways of pyrene degradation by Mycobacterium have also been identified Kim et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the ORF gi:119954364 (NidA3), encoding the terminal ␣ subunit of a ring-hydroxylation oxygenase, was most highly expressed when total peptides were counted. This ␣ subunit, with its ␤ subunit (NidB3), has been expressed in Escherichia coli, and its fluoranthene oxidation activity has been characterized (28). Surprisingly, the enzymes (PhtAaAbB) of the pht operon, hydroxylating phthalate to 3,4-dihydroxyphthalate, were increased after exposure of this strain to pyrene (29) but were not identified in the fluoranthene proteome.…”
Section: Continued On Following Pagementioning
confidence: 99%
“…Initially in M. vanbaalenii PYR-1, dioxygenation was reported to occur at the C-1,2 or C-7,8 position of fluoranthene, producing 9-fluorenone and acenaphthylene-1(2H)-one, respectively (23,26). Dioxygenation at C-2,3 also occurs in strain PYR-1 since recent molecular cloning and expression studies of NidA3B3, which codes for an initial ring-hydroxylating oxygenase, showed the transformation of fluoranthene to fluoranthene cis-2,3-dihydrodiol (28). In Mycobacterium sp.…”
mentioning
confidence: 99%
“…Therefore, the functional diversity and complexity of RHO systems for hydroxylation of LMW PAHs should be higher than those for HMW PAHs. Despite the exciting extension of knowledge of PAH metabolism, the epistatic interaction and pleiotropic activity of PAH-degrading enzymes, including RHO enzymes (30), are still poorly understood at the level of the metabolic network. Considering their extremely high functional redundancy with respect to LMW PAHs and, consequently, the increased epistatic and pleiotropic complexity of RHOs, it is challenging to annotate RHO enzymes into RCP functional modules and to understand the functional relationship of regulation/pleiotropy/epistasis of RHOs responsible for LMW PAHs in the PAH-MN.…”
mentioning
confidence: 99%
“…Considerable attention has been devoted in recent years to the identification and annotation of the ring-hydroxylating oxygenase (RHO) enzymes responsible for ring hydroxylation of HMW PAHs, the first step of the RCP module in the PAH-MN, which mainly controls the pathway and rate of degradation (25,(29)(30)(31). These endeavors have allowed evidence-based annotation of RHOs for the hydroxylation of HMW PAHs and also a better understanding of the effects of genetic perturbation and responses at a network level (25).…”
mentioning
confidence: 99%